Electronic Structure of Strongly Correlated Materials - Anisimov, Vladimir; Izyumov, Yuri.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Electronic structure and physical properties of strongly correlated materials containing elements with partially filled 3d, 4d, 4f and 5f electronic shells is analyzed by Dynamical Mean-Field Theory (DMFT). DMFT is the most universal and effective tool used for the theoretical investigation of electronic states with strong correlation effects. In the present book the basics of the method are given and its application to various material classes is shown. The book is aimed at a broad readership: theoretical physicists and experimentalists studying strongly correlated systems. It also serves as a handbook for students and all those who want to be acquainted with fast developing filed of condensed matter physics.
Electronic Structure Calculations in One-Electron Approximation -- Hubbard Model in Dynamical Mean-Field Theory -- DMFT Extensions -- Periodic Anderson Model (PAM) -- Electronic Structure Calculations for Real Materials by LDA + DMFT Method -- Conclusion.
Keywords: Microwaves; Optical materials; Materials Science; Optical and Electronic Materials; Condensed Matter Physics; Microwaves, RF and Optical Engineering